2003
DOI: 10.1136/pmj.79.932.352
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in rabies

Abstract: Rabies encephalitis has a classical clinical presentation and its diagnosis is unmistakable. In about a fifth of cases rabies occurs as its paralytic form, which lacks the classic symptoms and may mimic other diseases, especially acute disseminated encephalomyelitis (ADEM). Magnetic resonance imaging of the brain in rabies shows a distinct abnormal pattern that differentiates it from ADEM. Hence it may be a useful tool in diagnosis of paralytic rabies. Failure to administer post-exposure rabies immunoglobulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Neuroimaging studies may also be helpful, as shown by a few reports on MR imaging findings in rabies [26][27][28][29][30][31][32][33]. Nonenhancing ill-defined mild hyperintensities in the brain stem, hippocampi, hypothalami, deep and subcortical white matter, as well as deep and cortical gray matter were demonstrated on T2-weighted images.…”
Section: Rabiesmentioning
confidence: 90%
“…Neuroimaging studies may also be helpful, as shown by a few reports on MR imaging findings in rabies [26][27][28][29][30][31][32][33]. Nonenhancing ill-defined mild hyperintensities in the brain stem, hippocampi, hypothalami, deep and subcortical white matter, as well as deep and cortical gray matter were demonstrated on T2-weighted images.…”
Section: Rabiesmentioning
confidence: 90%
“…During prodromal and acute neurological (noncomatose) phase, predominant brain MRI findings include nonenhancing T 2 hyperintense foci variably involving the brain stem, hippocampi, deep and cortical gray matter, and subcortical white matter [3,9,10]. In comatose patients, there are additional findings of mild to moderate enhancement, especially in limbic structures, thalamus, brainstem, and deep gray nuclei [3,4,10]. Contrast enhancement is thought to represent blood-brain barrier leakage during the late phase of rabies when patients are clinically comatose [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…The MRI findings in cases of rabies infection vary considerably based on clinical severity [3][4][5][6][7][8][9][10]. During prodromal and acute neurological (noncomatose) phase, predominant brain MRI findings include nonenhancing T 2 hyperintense foci variably involving the brain stem, hippocampi, deep and cortical gray matter, and subcortical white matter [3,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Experience is limited with MR imaging, although normal studies and increased signals in gray matter areas have been observed [7][8][9][10][11]. Increased signals on T2-weighted images in the medulla and pons were observed in an American case in which disease was associated with a bat rabies virus variant [12].…”
Section: Investigationsmentioning
confidence: 97%